IκB kinase-induced interaction of TPL-2 kinase with 14-3-3 is essential for Toll-like receptor activation of ERK-1 and -2 MAP kinases - Ben-Addi, Abduelhakem (National Academy of Sciences, 2014)
The MEK-1/2 kinase TPL-2 is critical for Toll-like receptor activation of the ERK-1/2 MAP kinase pathway during inflammatory responses, but it can transform cells following C-terminal truncation. IκB kinase (IKK) complex phosphorylation of the TPL-2 C terminus regulates full-length TPL-2 activation of ERK-1/2 by a mechanism that has remained obscure. Here, we show that TPL-2 Ser-400 phosphorylation by IKK and TPL-2 Ser-443 autophosphorylation cooperated to trigger TPL-2 association with 14-3-3. Recruitment of 14-3-3 to the phosphorylated C terminus stimulated TPL-2 MEK-1 kinase activity, which was essential for TPL-2 activation of ERK-1/2. The binding of 14-3-3 to TPL-2 was also indispensible for lipopolysaccharide-induced production of tumor necrosis factor by macrophages, which is regulated by TPL-2 independently of ERK-1/2 activation. Our data identify a key step in the activation of TPL-2 signaling and provide a mechanistic insight into how C-terminal deletion triggers the oncogenic potential of TPL-2 by rendering its kinase activity independent of 14-3-3 binding.